Human papillomavirus vaccination and genital warts in young Indigenous Australians: national sentinel surveillance data. Issue 5 (20th March 2017) - Ali, Hammad; McManus, Hamish; O'Connor, Catherine C; Callander, Denton; Kong, Marlene; Graham, Simon; Saulo, Dina; Fairley, Christopher K; Regan, David G; Grulich, Andrew; Low, Nicola; Guy, Rebecca J; et al.
Abstract: Objectives: To examine the impact of the national human papillomavirus (HPV) vaccination program (available to girls and women [12–26 years] since 2007 and to boys [12–15 years] since 2013) on the number of diagnoses of genital warts in Australian Aboriginal and Torres Strait Islander (Indigenous) people. Design, setting, participants: Analysis of routinely collected data from patients attending 39 sexual health clinics (SHCs) in the Genital Warts Surveillance Network for the first time. Major outcome: The average annual proportion of Indigenous and non‐Indigenous SHC patients diagnosed with genital warts during the pre‐vaccination (2004–2007) and vaccination periods (2008–2014), stratified by age group and sex. Results: 7.3% of the 215 599 Australian‐born patients with known Indigenous status and seen for the first time at participating SHCs during 2004–2014 were Indigenous Australians. The average proportion of female Indigenous patients diagnosed with warts was lower during the vaccination period than during the pre‐vaccination period (in those under 21, summary rate ratio [SRR], 0.12; 95% CI, 0.07–0.21; P < 0.001); in 21–30–year olds: SRR, 0.41; 95% CI, 0.27–0.61; P < 0.001); there was no significant difference for women over 30 (SRR, 0.84; 95% CI, 0.51–1.36; P = 0.47). The proportion of male Indigenous heterosexual SHC patients under 21 diagnosed with warts was also lower during the vaccination period (SRR, 0.25; 95% CI, 0.12–0.49; P < 0.001), with no significant changes among older Indigenous men over 30. Conclusions: There were marked declines in the proportions of diagnoses of genital warts in young Indigenous women and men attending SHCs after the introduction of the HPV vaccination program. If high levels of HPV vaccine coverage are sustained, HPV‐related cancer rates should also decline.